(untitled) (Docentes 2.0 Journal, 2024)
Incorporating new educational methodologies has led to new challenges for schools related to the need for appropriate use of technology. The objective of this study was to analyze the use of digital technology by 6th EP and 1st ESO teachers and how they see their students using it. The inductive method was used, with a quantitative approach, experimental, descriptive, and cross-sectional design. The information collection procedure consisted of questionnaires sent to teachers of 6th EP and 1st ESO in the 2019-2020 academic year in a public institute in Castilla la Mancha (Spain). The sample corresponds to two centers attended by students from different city areas. The study analyzed the use of devices by teachers who teach in 6th EP and 1st ESO and how they perceived their students using the network. It was concluded that teachers’ safe use of the network is essential for protecting the privacy and security of students. The questionnaire was previously subjected to expert judgment. Teachers need training and information to educate their students safely and responsibly using the network and integrating digital tools and resources safely and responsibly in teaching-learning.